(untitled) (Annals of Medical Research, 2024)
Aim: This study investigates the association of complete blood count parameters and erythrocyte transfusions with retinopathy of prematurity (ROP) requiring treatment in infants born prematurely under 32 weeks of gestation. Materials and Methods: The single-center, retrospective, observational study included 130 patients with a gestational age between 24-32 weeks who were born in the same hospital and hospitalized in the neonatal intensive care unit of the hospital between 2016-2018. Results: Mean complete blood count parameters at postnatal 0-24 hours and postnatal 24-72 hours as well as erythrocyte transfusions were compared in terms of retinopathy of prematurity requiring treatment. Mean hemoglobin, hematocrit and red blood cell count at postnatal 24-72 hours were significantly lower in patients with ROP requiring treatment than in those without. Conclusion: The study suggests that low erythrocyte mass and an increased number of early erythrocyte transfusions are important risk factors for the development of ROP requiring treatment.